Some assembly required : the not-so-secret life of a transgender teen - Andrews, Arin (Simon & Schuster BFYR, 2014)
"Seventeen-year-old Arin Andrews shares all the hilarious, painful, and poignant details of undergoing gender reassignment as a high school student in this winning teen memoir"--